The dialogical myth. A conversational analysis of philosophical dialogue - González de Requena Farré, Juan Antonio (Estudios de Filosofía, 2012)
The idealization of dialogue is not only a characteristic gesture of contemporary philosophical thought, but also of the humanities and of the pedagogical, therapeutic and organizational intervention procedures. In this article, we provide a critical review of the founding myth of Socratic dialogue through a conversation analysis of movements and discourse functions which are developed in it. In addition, we will explore the modern evolution of the genre of philosophical dialogue.